The impact of quality of work-life and burnout on employee performance with job satisfaction as an intervening variable (case study on employees of pt inkabiz indonesia) - Aulia, Putri Zahra; Yaman, Bahrul (Institute of Computer Science (IOCS), 2024)
The purpose of this study is to examine the effect of work-life quality and burnout on employee output combined with contentment at work as a mediating variable. This is a quantitative research study with 85 PT Inkabiz Indonesia employees as the sample. A probability sampling combined with simple random sampling was the sample method employed. A questionnaire was used to gather data, which SmartPLS software assisted in analyzing using partial least squares (PLS). The study's findings indicate that: 1) job satisfaction is significantly impacted by quality of work-life; 2) burnout is significantly impacted by quality of work-life; 3) quality of work-life is significantly impacted by performance; 4) burnout is significantly impacted by performance; 5) job satisfaction is greatly influenced by performance; 6) quality of work-life is significantly impacted by performance combined with contentment in one's work acting as an intervening variable; and 7) burnout is significantly impacted on output and contentment in one's work acting as an variable